2020
DOI: 10.1021/acs.inorgchem.9b03496
|View full text |Cite
|
Sign up to set email alerts
|

Multiresponsive Luminescent Sensitivities of a 3D Cd-CP with Visual Turn-on and Ratiometric Sensing toward Al3+ and Cr3+ as Well as Turn-off Sensing toward Fe3+

Abstract: By using the reduced Schiff base tricarboxylate ligand H 3 cip, one novel 3D Cd-based coordination polymer (Cd-CP) with the formula [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (H 3 cip = 5-(3-carboxybenzylamino)isophthalic acid, bpea = 1,2-bis(4-pyridyl)ethane) has been solvothermally synthesized. The prepared Cd-CP possesses a 4-connected CdSO 4 net based on dinuclear {Cd 2 } units. Luminescence measurements revealed that the complex exhibited ratiometric turn-on luminescence responses toward Al 3+ and Cr 3+ with a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 69 publications
2
60
0
Order By: Relevance
“… MOF compounds Sensing targets LOD Number of recycles Ref a. Metal ion sensors NH 2 -MIL-125(Ti) Pb 2+ 0.70 × 10 −2 nM 5 [405] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Fe 3+ 3.24 µM 5 [406] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Al 3+ 1.31 µM 5 [406] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Cr 3+ 1.84 µM 5 [406] MOF NU-902 Cd 2+ 0.3 ppb [407] MOF NU-902 PVC membrane Cd 2+ [407] CAU-10-V-H Pd 2+ 110 nM 5 [408] MIL-53(Al)–NH2-MPA Fe 3+ 0.36 µM [416] [[Zn(4,4′-AP)(5-AIA)]. (DMF)0.5] n Hg 2+ 0.01 nM [409] b. Anion sensors TMU-41 Cr 2 O 7 2− 0.02 µM 4 [410] TMU-41 CrO 4 2− 0.03 µM 4 [410] …”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
See 1 more Smart Citation
“… MOF compounds Sensing targets LOD Number of recycles Ref a. Metal ion sensors NH 2 -MIL-125(Ti) Pb 2+ 0.70 × 10 −2 nM 5 [405] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Fe 3+ 3.24 µM 5 [406] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Al 3+ 1.31 µM 5 [406] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Cr 3+ 1.84 µM 5 [406] MOF NU-902 Cd 2+ 0.3 ppb [407] MOF NU-902 PVC membrane Cd 2+ [407] CAU-10-V-H Pd 2+ 110 nM 5 [408] MIL-53(Al)–NH2-MPA Fe 3+ 0.36 µM [416] [[Zn(4,4′-AP)(5-AIA)]. (DMF)0.5] n Hg 2+ 0.01 nM [409] b. Anion sensors TMU-41 Cr 2 O 7 2− 0.02 µM 4 [410] TMU-41 CrO 4 2− 0.03 µM 4 [410] …”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
“…Thus, research has been conducted into the development of selective and sensitive sensor probes for their detection. A Cd-based coordination polymer ([Cd(Hcip)(bpea) 0.5 ·(H 2 O)] n , denoted as Cd-CP) was prepared recently for sensing these metal cations [406] . The researchers analyzed the fluorescence signals at various metal ion concentrations, and found that the Cd-CP MOF shows detections limits of 1.31, 1.84, and 3.24 µM for Al 3+ , Cr 3+ , and Fe 3+ , respectively.…”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
“…30,31 Luminescent MOFs (LMOFs) are a major category of MOFs, which are considered to be potential candidates as sensor materials to detect multiple substances, including heavy metals, 32 explosives, 33 and toxicants. 34 Compared with other luminescence materials, LMOFs have numerous excellent advantages, including multiple light sources, large Stokes shift, high luminance, stability, and host-guest interaction. The porous nature of LMOFs can enrich the guest analyte in LMOFs by capturing the trace analyte to enhance the sensing performance.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Being paramagnetic in nature, Fe 3 + detection by fluorescence probes results in quenching of emission intensity which may limit the detection. [12][13][14] Different types of sensors have been developed for detection of Fe 3 + ion that include optical fiber, [15,16] colorimetric, [17][18][19][20][21] potentiometric, [22,23] MOF-based, [24][25][26][27] electrochemical, [28][29][30] polymer-based [31,32] and fluorescent sensors. [33][34][35][36][37] Many traditional techniques were also used to detect Fe 3 + ions, such as atomic absorption spectroscopy (AAS), [38] inductively coupled plasma -mass spectroscopy (ICP-MS), [39] spectrophotometry, [40] voltammetry, [41] extraction spectrophotometry (ES) and resonance scattering spectrometry.…”
Section: Introductionmentioning
confidence: 99%